Early evidence of avocado domestication from El Gigante Rockshelter, Honduras - Amber M. VanDerwarker; Heather B. Thakar; Kenneth Hirth; Alejandra I. Domic; Thomas K. Harper; Richard J. George; Emily S. Johnson; Victoria Newhall; Timothy E. Scheffler; Weston C. McCool; Kevin Wann; Brandon S. Gaut; et al. (Proceedings of the National Academy of Sciences, 2025)
Molecular research suggests that avocados ( Persea americana Mill.) were domesticated multiple times in the Americas. Seed exchange, hybridization, and cloning have played an essential role across their wild distribution from Mexico to South America to create the modern varieties of today. Archaeological sites with well-preserved and directly radiocarbon-dated botanical assemblages are rare, however, so we know very little about the complexities of the domestication process. Here, we define an early locus of avocado domestication using well-dated desiccated and carbonized avocado remains from El Gigante rockshelter in western Honduras spanning the last 11,000 y. Measurements of avocado seeds and rinds show evidence for long-term management resulting in selection for larger, more robust fruits through time that culminated by 2,250 to 2,080 calendar B.P. (cal. B.P.). However, human-directed selection for larger fruits with thicker rinds is evident as early as 7,565 to 7,265 cal. B.P. Seed morphology is similar to P. americana var. guatemalensis and is congruent with genetic data for the development of this variety in both the highlands of Guatemala and Honduras. Increases in seed size and rind thickness through time are consistent with genetic evidence for the enrichment of putative candidate genes for fruit development and ripening in this variety.